Investigation and Evaluation of different Combined Heat and Power Configurations - Vergos, Konstantinos (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Θερμότητας, 2014)
Geothermal Energy has the potential to provide a low CO2 emission base-load power and heat by utilizing the natural hydrothermal resources of the planet. Moreover, the exploitable hot spots are worldwide distributed and have the potential to satisfy the world energy demand. Most of the widely distributed exploitable geothermal sources consist of low-temperature water in the range of 100-140 °C. In this range, an effective and widely used technology is the Organic Rankine Cycle (ORC). The interest in the development and research of ORC units had a tremendous increase in the last decade, due to the wide scope of applications it can be used for. Geothermal plants, Waste Heat Recovery, Biomass Plants and Solar Thermal Plants are the main driving force behind the continuing increase in the interest in the ORC technology. In the present study, MATLAB simulations were developed for the investigation of ORC units with different component configurations as well as with different HFOs as the working fluid. Furthermore, a detailed economic analysis was carried out, in order to assess the economic feasibility of each configuration.